Socialised to think in terms of left and right? The acceptability of the left and the right among European voters. (August 2021) - Otjes, Simon; Rekker, Roderik
Abstract: The left-right dimension plays a crucial role in how political scientists think about politics. Yet we know surprisingly little about the extent to which citizens are able to position themselves on a left-right dimension. By analysing non-response on left-right self-identification question from seven waves of the European Social Survey ( N = 295, 713), this study demonstrates that citizens' ability to position themselves on the left-right dimension depends on the political system they live in and its history. Citizens in countries with lower levels of elite polarization place themselves on a left-right dimension less often, this difference is partiularly pronounced for citizens with high levels of political interest. Citizens in countries with a recent authoritarian history were unable to place themselves on the left-right dimension more often. These findings show the importance of political socialization for left-right self-identification.